Optimizing green knowledge acquisition through entrepreneurial orientation and resource orchestration for sustainable business performance - Baquero, Asier (Marketing Intelligence & Planning, 2024)
Purpose: Considering the importance of green knowledge in firms' sustainability, this study investigates the mediating mechanism of green knowledge acquisition (GKA) and the moderating role of resource orchestration capability (ROC) in the relationship between green entrepreneurial orientation (GEO) and corporate sustainable performance (CSP). Design/methodology/approach: Using a sample of 388 executives from 195 small and medium-sized enterprises (SMEs) in the UAE, this study used partial least squares structural equation modelling to examine the proposed relationships among the constructs. Findings: The research shows that GEO affects CSP's environmental, economic, and social aspects of CSP. This study also highlights the mediating role of GKA in the relationship between GEO and CSP. The moderated mediation analysis results indicate that when ROC is elevated, GEO's indirect influence on environmental and economic performance through GKA is more pronounced. Practical implications: This study provides useful insights and a novel approach for manufacturing industries and authoritative bodies to alleviate environmental deterioration and improve CSP by encouraging GKA through green entrepreneurship. Originality/value: This study enriches the existing literature on GEO, GKA, and CSP by focusing on environmental challenges and applying the resource-based view (RBV) framework. The study's findings broaden the theoretical basis for green entrepreneurship, provide guidance on enhancing CSP in manufacturing firms, and advance green entrepreneurship research.
Keywords: green entrepreneurial orientation; green knowledge acquisition; corporate sustainable performance; resource orchestration capability